IZIN PENGANGKATAN BENDA BERHARGA ATAS MUATAN KAPAL TENGGELAM (BMKT) SEBAGAI INSTRUMEN KONSERVASI SUMBER DAYA LAUT DI INDONESIA - Lilik Pudjiastuti; Franky Butar-Butar (Yuridika, 2010)
The writing is aimed to know the management of marine resources related to the business of making objects of cargo ship sank in Indonesian waters. This is related to obligatory countries in meeting the public’s right to good environment as stated in Article 28 H of the Indonesia Constitution of 1945. In fact this is now the object decision activity on cargo ship sank materials often done by a person or a foreign business entity that tried to search for treasure in Indonesia, this will be detrimental to objects of cultural heritage in Indonesia and can make damage or environmental pollution. Thus the need for government facilities that can control these activities, one means that governments use to control is through the permit retrieval objects loads up sink ships. The principle that should be applied in making the management of the objects sinking ship include: (i) legislation to permit, (ii) the issuance of permits, (iii) to permit law enforcement, and (iv) the responsibilities of government (publisher permission). Research and writing of this normative approach that starts from the legislation on marine resource management and licensing in the starter making objects cargo ship sank and regional governance. The results of this study will describe the relationship between objects permits retrieval of cargo ship sunk as a means to control the objects that fall into objects of cultural heritage and effort to of control pollution of the in marine environment in Indonesia.